Reflection of Fictional Space Design on Fashion Brands: The Case of Balenciaga Afterworld Video Game - Öztekin, Mertcan; Kavut, İsmail Emre (Journal of Interior Design and Academy, 2022)
Fiction is the realization of a dream in a concrete or abstract medium. This action is formed by the design of fictional space in architecture. Some spaces used in fashion brands are examples of fictional space design. Brands reflect the philosophy of life they give to the individual with their identities, both on the products and on the presentation of the products. It is aimed to be a preferred brand with a positive effect on users. The spaces belonging to the brand are shaped by fictional narration and guide to this goal. Sensory perceptions of fictional spaces affect individuals positively and provide a bonding institution with the brand. With the developing technology, fictional spaces are designed on the digital platform and a gamified experience is offered to fashion brands. The venues in the video game "Afterworld", designed for the 2021 fall-winter collection of the Balenciaga brand in the fashion industry, which is considered to have a high creative power, considering the corporate identity expression, recognition and impact level, were examined. In the study, the reflection of the fictional spaces in fashion brands, which are handled with the qualitative research method, on the space design by creating an experiential positive effect has been investigated.